PENGARUH SUKUK TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Muhammad Ardi (UIN Mataram, 2018)
This study aims to find out how the influence of sharia sukuksukuk on economic growth and analyze the implementation of sukuk growth from 2002 to 2015. It turns out that from year to year, investors are increasing in sukukijarah according to secondary data obtained from statistics. This study uses a quantitative approach is a descriptive method and verification of case study approach. this article is a quantitative article. This paper is library research, Analysis of the paper data used is content analysis. The results of the hypothesis from the authors that sukukhijarah affect economic growth.